2014
DOI: 10.1016/j.eurpsy.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of family characteristics and bipolar disorder using causal-pie models

Abstract: Many family characteristics were reported to increase the risk of bipolar disorder (BPD). The development of BPD may be mediated through different pathways, involving diverse risk factor profiles. We evaluated the associations of family characteristics to build influential causal-pie models to estimate their contributions on the risk of developing BPD at the population level. We recruited 329 clinically diagnosed BPD patients and 202 healthy controls to collect information in parental psychopathology, parent-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Family functioning is often poor for those with bipolar disorder (43). In prospective research, family impairment has been shown to predict depressive more than manic symptoms among adults (39, 44, 45).…”
Section: Low Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Family functioning is often poor for those with bipolar disorder (43). In prospective research, family impairment has been shown to predict depressive more than manic symptoms among adults (39, 44, 45).…”
Section: Low Social Supportmentioning
confidence: 99%
“…Causal interpretations of family functioning on the course of adolescent bipolar disorder, however, must be approached cautiously. One of the strongest predictors of risk of bipolar disorder is parental psychopathology (43). In addition, family conflict may arise as parents attempt to exert control over the manic symptoms they observe in their children.…”
Section: Low Social Supportmentioning
confidence: 99%
“…Variables entered into the model included all those with a P ≤0.2 from the univariate analyses. SUD, whether present in the family or in the patient, even if the P >0.2, was also entered into the model of analysis because of its theoretical association with BD 23. In the final step of the regression analysis, the variables that still had a statistical significant positive association with AD comorbidity were age at onset of BD (odds ratio =0.95, 95% confidence interval [CI] =0.93–0.97, P <0.01), SUD in the patient’s family (odds ratio =2.18, 95% CI =1.11–4.27, P =0.02), and a higher MADRS (odds ratio =1.10, 95% CI =1.06–1.15, P <0.01) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with previous reports in of poorer outcomes in offspring of BD probands with SUD. 32,40 This strongly suggests a need for early intervention with parents with BD and SUD, and suggests that treatment interventions for parents with this comorbidity is an important part of treating their offspring who are presenting with Axis I disorders as well. Finally, OBD with comorbid Axis I diagnoses who had personal diagnosis of MDD or BD also reported more frequent independent stressful life events.…”
Section: Discussionmentioning
confidence: 99%